ANALISIS TANDA DALAM FILM FANTASTIC BEAST : THE CRIMES OF GRINDELWALD KARYA DAVID YATES (SEBUAH ANALISIS SEMIOTIK) - Tendean, Oktaviani Nolla; Rambing, Rosalina; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â  Â  This research entitled â€œAnalisis Tanda Dalam Film Fantastic Beast : The Crimes of Grindelwald Karya David Yatesâ€. The aims of this research are to identify and classify the kind of signs as well as to analyze the meanings of signs used in the film Fantastic Beast : The Crimes of Grindelwald. The writer uses the theory of Charles Sanders Pierce (1995) in the process of identifying, classifying, and analyzing each sign and the meaning of signs in Fantastic Beast : The Crimes of Grindelwald. The method used in this study is a descriptive method. In doing this research, the writer read some journals, books, and articles about signs. The data were collected by the writer from film Fantastic Beast : The Crimes of Grindelwald by watching, finding, and taking the piece of images that contain the signs, and then classifying them based on its kinds from the film. The classified data were analyzed to find out the meaning. The result of this research shows that based on the theory of Pierce (1995) there are three kinds of signs, namely icons, index, and symbols. Those are 7 icons, 12 indexes, 7 symbols. They were found from 26 scenes in the film Fantastic Beast : The Crimes of Grindelwald and each signs has different meaning.Keywords: Sign, Fantastic Beast : The Crimes of Grindelwald, Semiotic Analysis